Study of foreign experience in providing public services in the field of tourism: implementation possibilities for sustainable development (Economics and region, 2025)
The article examines the foreign experience of organizing public services in the field of tourism using the examples of France, Italy, Spain, Estonia and Portugal. It is shown that public tourism services include administrative, information, regulatory and digital services aimed at developing territories, improving the quality of life and creating a competitive tourism product. The key models based on the concepts of smart tourism, public-private partnership and sustainability orientation are highlighted. The challenges of implementing international practices in Ukraine are outlined, taking into account the consequences of the war, in particular the destruction of infrastructure, lack of funding and institutional fragmentation. Prospects for the use of digital platforms, community-based tourism and European support mechanisms for the restoration and modernization of the tourism sector of Ukraine are identified.
Keywords: public services; tourism; sustainable development; foreign experience; public administration; digitalization; war